Prinsip Dasar Sistem Ekonomi Islam - Ilyas, Rahmat; Hermanto, Hermanto (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
The Islamic economic system is a separate economic system, not a combination and or mixture of capitalist and socialist economic systems. The Islamic economic system places humans not as central (anthropocentrism) but as servants of God (âbid) who must serve and carry out the tasks entrusted to Him as servants (khalîfah). For this reason, economic activities must uphold the values of ownership, the values of justice, freedom, balance, and brotherhood and togetherness in accordance with the guidance of religious teachings in order to create a personal and social life and a good state. In the eyes of Islam, economics is not the ultimate goal of human life, but is a completeness in life, a means to achieve higher goals, supports and services for aqidah and the mission it carries.